Assessment of antimicrobial, insecticidal and genotoxic effects of Melia azedarach L. (chinaberry) naturalized in Anatolia - Orhan, Ilkay Erdogan; Guner, Elif; Ozcelik, Berrin; Senol, Fatma Sezer; Caglar, Selim Sualp; Emecen, Guzin; Sener, Bilge (Informa Healthcare, 2012)
In this study, antibacterial, antifungal, insecticidal and genotoxic activities of the fruit and leaf extracts of Melia azedarach of Turkish origin were evaluated for the first time. The antimicrobial activity was assessed against Gram (+) and (-) bacteria, four Candida species and three dermatophytic fungus (Trichophyton rubrum, Epidermophyton floccosum and Microsporum gypseum). The insecticidal activity of the methanolic fruit extract was performed against the larvae of Aedes aegpyti, Culex pipiens and Culex quinquefasciatus. The genotoxicity of this extract was evaluated against Drosophila melanogaster by somatic mutation and recombination test. The extracts showed higher antibacterial effect against Gram (-) strains (16-32 mu g ml(-1) of minimal inhibition concentration, MIC), while the leaf extracts were more effective on Candida albicans (32 mu g ml(-1) of MIC). The extracts did not exhibit insecticidal activity and genotoxicity. Total phenol and flavonoid contents of the extracts were determined spectrophotometrically, and the ethyl acetate extract of the leaves was the richest in total flavonoids.
Keywords: Melia azedarach; antimicrobial activity; insecticidal activity; genotoxicity